PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAN SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN SEKTOR PERINDUSTRIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Josua Putra Prahdya Nababan; Jeudi A.T.P. Sianturi; Wesly A. Simanjuntak (STKIP Subang, 2026)
This study aims to obtain empirical evidence of firm size in mediating the effect of capital structure, profitability, and dividend policy on firm value. The sampling method used purposive sampling from industrials sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. A total of 42 companies met the criteria. The analysis software used is WarpPLS 8.0. The results show that capital structure has a positive and significant effect on firm value. Profitability and dividend policy have a positive but not significant effect on firm value. Capital structure and dividend policy have a positive and significant effect on firm size, while profitability has a negative and insignificant effect on firm size. Firm size has a positive and significant effect on firm value. The test results prove that firm size is able to partially mediate the effect of capital structure on firm value, and fully mediate the effect of profitability and dividend policy on firm value.